Study of self-compacting concrete containing coal bottom ash and fly ash. Issue 1 (1st April 2022) - Adnan, Mohd.; Kumar, Ankit; Kant, Kunal; Aggarwal, Paratibha; Aggarwal, Yogesh
Abstract: This paper consists of a detailed analysis of the use of industrial by-products(coal bottom ash and fly ash) as an admixture in the self-compacting concrete. The judicious use of industrial byproducts and the proper waste management can lead to a sustainable development in the field of infrastructure. This paper talks about the physical and chemical properties of these by products used in the self-compacting concrete. Critical and definite analysis has been carried out on the reviewed literature and further scope of work in the analysis and interpretation has been addressed. On a positive note, it can be stated that the use of industrial by-products in self-compacting concrete can lead to a sustainable development.